Education for a Clean and Healthy Lifestyle as an Effort to Prevent Covid-19 Through KKN Activities - Badriyah, Siva Faizatul; Octaviani, Widya Tatalia; Rahmaningtyas, Wisudani; Supriyatno, Teguh; Kurniaziz, Septian Bagas Panji (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Recently, Covid cases in Indonesia have experienced a significant decline, but in mid-2021, precisely after the Eid al-Fitr holiday, Covid cases in Indonesia increased sharply. Pati Regency is one of the areas with black zone status. It was recorded that there were 151 RTs spread across 38 villages in 11 sub-districts forced to local lockdown. This is exacerbated by the low public awareness of the importance of health for themselves. A strategy is needed from both the government and the local community to prevent the spread of the corona virus. One of the efforts that can be done is through outreach activities and mentoring for a Clean and Healthy Lifestyle (PHBS). PHBS behavior is a behavior or health action that is carried out on the awareness of each family member and plays an active role in activities in the community. Through education from the KKN UNNES student group, it is hoped that the community in Soneyan Village, Margoyoso District, Pati Regency will realize the importance of clean and healthy lifestyle behavior through several programs. The steps in the education program that were carried out included counseling on how to wash hands properly and correctly, counseling on the use of hand sanitizers and socializing how to make hand sanitizer using natural ingredients. The results show that there is a change in knowledge in the community, besides that the evaluation process shows a change in people's behavior that is more concerned with cleanliness and health.